Modelling and simulation of an on grid 100-kW photovoltaic system - Adnan Majeed Abed; Afaneen Anwer Alkhazraji; Shatha Suhbat Abdulla Al-Kubragyi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
This work proposes a design of a solar radiation generator system to extract a maximum power of 100 kilowatts for the uses of 400 volts, 50 Hertz electrical network, under standard conditions (1000 Watts/m2 and 25 Â°C). The main goal is to inject and control active and reactive power to the grid by a three-phase, one-stage solar grid-connected 100-kW photovoltaic (PV) plant, to keep the current's total harmonic distortion (THD) within the international requirements, and maintain a constant voltage regardless of solar radiation changes. This design consists of three control loops those are: the maximum power point tracking (MPPT), the DC-link voltage, and the current controller. The proposed system was simulated in MATLAB/Simulink environment and was applied on part of the Baghdad electrical network. The obtained results showed the efficiency of the proposed design and modelling.